The Role of Vowels and Consonants In English Language Learning - Lubis, Yani; Ramadhany, Cindy Alia; Widyana, Airen; Mahara, Elvida Futri; Sarahseti, Dian Fanny (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Numerous studies indicate that consonants are more highly valued for lexical interpretation than vowels because of the richer and more powerful distinctions they can make. Consonants appear to be the most important phoneme for differentiating between lexical items in most language systems. Cross-linguistically, consonants are more common than vowels. The title "The Role Of Vowels And Consonants In English Language Learning" would be better served by a descriptive study. The purpose of this research is to examine how consonants function in language development, with an emphasis on their articulation and acquisition. The purpose of a descriptive study is to provide readers a thorough grasp of the subject of the investigation. Learners who experience immersion language situations or early exposure to English tend to acquire consonants more quickly. It is crucial to remember that every learner is different when it comes to the acquisition of consonants, and some students may find it difficult to make particular sounds correctly. The phonetic variations between the learner's native language and English may have an impact on this, making it harder for them to recognize and produce novel sounds.